Information technology and higher education institutions (HEI) performance: the mediating role of organizational capability - Marlina, Evi; Lawita, Nadia Faturrahmi (Journal of Accounting and Investment, 2024)
Research aims: This study aims to examine the effect of Information Technology (IT) on the performance of Higher Education Institutions (HEIs) in Indonesia. Also, this study investigates organizational capability as a mediating variable.Design/Methodology/Approach: This research was conducted at HEIs covering all regions in Indonesia, namely Sumatra, Java, Kalimantan, Sulawesi, Nusra, and Bali, as well as Papua. The research sample was 368 HEIs. The data were obtained by distributing questionnaires, and hypothesis testing was conducted using the Partial Least Square (PLS) method. Research findings: The study revealed that IT positively affected organizational capability and HEI performance. Organizational capability yielded a positive effect on HEI performance. Furthermore, organizational capability mediated the effect of IT on HEI performance.Theoretical contribution/ Originality: This study contributes to the research area dealing with IT, HEIs performance, and organizational capability as a mediating variable. Practitioner/Policy implication: HEI managers should improve their IT resources to enhance organizational capability, thereby improving organizational performance.Limitation/Implication: The limitation of the study is that the data collection only used questionnaires, so the information obtained was not in-depth.